2021
DOI: 10.3390/cancers13184552
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 2A Expression in Cancer-Associated Fibroblasts and Cancer Cells Promotes Esophageal Squamous Cell Carcinoma Progression

Abstract: Esophageal cancer has the sixth highest mortality rate worldwide. Cancer-associated fibroblasts (CAFs) are involved in the progression of various cancers. Previously, we demonstrated an association between high expression of the CAF marker, fibroblast activation protein, and poor prognosis of esophageal squamous cell carcinoma (ESCC). We also established CAF-like cells by indirect co-culture of bone marrow-derived mesenchymal stem cells with ESCC cell lines and found metallothionein 2A (MT2A) to be highly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…A Japanese researcher found that MT2A was highly expressed in CAF cells constructed by them. Knockdown of MT2A inhibited the expression and secretion of insulin-like growth factor binding protein 2 (IGFBP2), and recombinant IGFBP2 promoted the migration and invasion of ESCC cells through NF-κB, Akt and Erk signaling pathways ( 57 ). The opposite effect of MTs in different tumors may be related to tumor type and differentiation, other environmental stimuli or gene mutations ( 13 ).…”
Section: Disscusionmentioning
confidence: 99%
“…A Japanese researcher found that MT2A was highly expressed in CAF cells constructed by them. Knockdown of MT2A inhibited the expression and secretion of insulin-like growth factor binding protein 2 (IGFBP2), and recombinant IGFBP2 promoted the migration and invasion of ESCC cells through NF-κB, Akt and Erk signaling pathways ( 57 ). The opposite effect of MTs in different tumors may be related to tumor type and differentiation, other environmental stimuli or gene mutations ( 13 ).…”
Section: Disscusionmentioning
confidence: 99%
“…Silencing of MT2A-inhibited cell growth by inducing cell cycle arrest in the G1-phase (G1-arrest) involving the ATM/Chk2/cdc25A pathway [21]. In esophageal cancer, high immunoexpression of MT2A is associated with a high pathological stage, lymph node metastasis, and lymphovascular invasion [22]. In vitro, MT2A knockdown in cancer cells (TE-10 and TE-11) inhibited the malignant phenotype by increasing E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 secreted by FAP + CAFs not only can promote ESCC cell invasion and EMT but also can recruit FoxP3 + T cells and induce TAM M2 polarization to promote metastasis ( 81 , 82 ). The presence of CAFs in ESCC patients is associated with increased micro-vessel density, TAMs, and EMT, which are critical for ESCC invasion and metastasis ( 83 , 84 ). A number of genes have been shown to promote ESCC invasion and metastasis via the CAF transformation and EMT process ( 85 , 86 ).…”
Section: The Role Of Tumor Microenvironment In Esophageal Squamous Ce...mentioning
confidence: 99%